2007
DOI: 10.1021/np0703747
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Aspidofractinine, Rhazinilam, Akuammiline, and Vincorine Alkaloids from Kopsia

Abstract: Eleven new indole alkaloids, in addition to the previously reported rhazinal (1), and 14 other known alkaloids, were obtained from the Malayan Kopsia singapurensis, viz., kopsiloscines A-F (2-7), 16-epikopsinine (8), kopsilongine- N-oxide (9), 16-epiakuammiline (10), aspidophylline A (11), and vincophylline (12). The structures of these alkaloids were determined using NMR and MS analyses. Rhazinal (1), rhazinilam (17), and rhazinicine (18) showed appreciable cytotoxicity toward drug-sensitive as well as vincri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 47 publications
2
97
0
5
Order By: Relevance
“…Notably, ψ-akuammigine (9) contains an additional ring that forms a complex [3.2.1]-bridged oxabicyclic motif. The second group is composed of the furanoindolinecontaining akuammilines and is represented by aspidophylline A (10), 12 aspidodasycarpine (11), 13 and aspidophylline B (12). 14 Members of this group contain an oxygen linkage between C5 and C2 as a salient feature of their furanoindoline cores but lack the N4−C5 bond found in the parent methanoquinolizidine akuammilines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Notably, ψ-akuammigine (9) contains an additional ring that forms a complex [3.2.1]-bridged oxabicyclic motif. The second group is composed of the furanoindolinecontaining akuammilines and is represented by aspidophylline A (10), 12 aspidodasycarpine (11), 13 and aspidophylline B (12). 14 Members of this group contain an oxygen linkage between C5 and C2 as a salient feature of their furanoindoline cores but lack the N4−C5 bond found in the parent methanoquinolizidine akuammilines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Alkaloids 5−8 were dihydroindole derivatives with the same extended fused ring system, which is a new skeleton. HREIMS of 5−8 provided molecular formulas of C 20 (M + 366.1977), and C 21 H 24 N 2 O 4 (M + 368.1720), respectively. The aromatic proton and carbon resonances (HSQC and HMBC) indicated that 5 was a 12-hydroxy-N-acyldihydroindole derivative, 6 was a 12-hydroxy-10-methoxy-N-acyldihydroindole derivative, 7 was a 12-hydroxy-N-butanoyldihydroindole derivative, and 8 was a 12-hydroxy-11-methoxy-N-acyldihydroindole derivative ( Table 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Crocacins were found to exhibit moderate antibacterial, antifungal, and cytotoxic activity. The synthesis of the dienamide moiety of the natural product was performed via a one-pot palladium-catalyzed sequence involving a hydrostannylation and a Stille coupling of 52 with (E)-iodoacrylamide (53). This one-pot procedure circumvented the purification of the intermediate vinylstannane 54, avoiding the partial protodestannylation of the product.…”
Section: Total Synthesis Of Various Classes Of Natural Productsmentioning
confidence: 99%